2019
DOI: 10.1007/978-3-030-32875-7_11
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Preterm Birth Markers with U-Net Segmentation Network

Abstract: Preterm birth is the most common cause of neonatal death. Current diagnostic methods that assess the risk of preterm birth involve the collection of maternal characteristics and transvaginal ultrasound imaging conducted in the first and second trimester of pregnancy. Analysis of the ultrasound data is based on visual inspection of images by gynaecologist, sometimes supported by hand-designed image features such as cervical length. Due to the complexity of this process and its subjective component, approximatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Nerve segmentation [151], [222] Base U-net [50] Inception block [223] Residual block [224] Modified parallel U-net Breast lesion [225] Base U-net [39] Attention gate Arterial wall [226] Base U-net Cardiovascular structures [227] Base U-net Fetal head [219] Base U-net Gastrointestinal tumor [228] Base U-net Knee cartilage [96] Modified U-net with dual parallel encoders Preterm birth prediction [220] Base U-net Thyroid [229] Residual block Transcranial detection [221] Base U-net Ovary detection [230] Base U-net…”
Section: Reference Model/methods Usedmentioning
confidence: 99%
“…Nerve segmentation [151], [222] Base U-net [50] Inception block [223] Residual block [224] Modified parallel U-net Breast lesion [225] Base U-net [39] Attention gate Arterial wall [226] Base U-net Cardiovascular structures [227] Base U-net Fetal head [219] Base U-net Gastrointestinal tumor [228] Base U-net Knee cartilage [96] Modified U-net with dual parallel encoders Preterm birth prediction [220] Base U-net Thyroid [229] Residual block Transcranial detection [221] Base U-net Ovary detection [230] Base U-net…”
Section: Reference Model/methods Usedmentioning
confidence: 99%
“…In [165], a U-Net is used to segment the cervix from US images. The masks obtained are used to estimate the cervical length and the anterior cervical angle.…”
Section: Other Tasksmentioning
confidence: 99%
“…While predictive machine learning (ML) models have enjoyed an ever-increasing popularity, preterm birth has only been addressed as a classification problem. Models based on electronic health records, uterine electromyography and transvaginal February 6, 2024 3/24 ultrasound [47] reported accuracies of approximately 0.77 [48][49][50], while studies based on electrohysterography reported values above 0.94 [51][52][53], with the latter, however, only including records of women with recorded contractile activity [53,54].…”
Section: Introductionmentioning
confidence: 99%